Ecospirituality in Forensic Mental Health: A Preliminary Outcome Study - Clark Patrick Heard; Jared Scott; Stephen Yeo (Scholarworks @ WMU, 2022)
Background: In this study, the personal experience of spirituality in nature (the concept of ecospirituality) was supported by occupational therapy and spiritual care staff enabling a community-based group for persons affiliated with a forensic mental health system in Ontario, Canada. Spirituality is a key, though debated, tenet in occupational therapy practice. At the same time, immersive participation in nature has been linked to positive health outcomes. Methods: A qualitative method consistent with Interpretative Phenomenological Analysis was employed. Data was collected via the completion of semi-structured interviews (n = 9). Collected data was transcribed verbatim and then coded for themes by multiple coders. Several methods were employed to support trustworthiness. Results: Results identified that participation in the ecospirituality group enabled the participants to feel an enhanced connection with nature and an opportunity for unguarded reflection and relaxation. The participants described a regenerative and restorative experience, including a sense of peace and connection with the personally sacred. Enhanced resiliency and meaningful connection with others also were identified. Conclusion: Recommendations related to outcomes are identified. These include a focus on enhanced access to natural environments for individuals involved in mental health systems. Just as importantly, the opportunity for personal agency and autonomy in those settings appears indicated.